Acetic acid lignin-plant fiber composite material as well as preparation method and application thereof
By preparing lignin acetate-plant fiber composite materials, the environmental problems of honeycomb substrates are solved, and high-strength, biodegradable and low-cost honeycomb materials are achieved, which are suitable for aerospace, transportation, building decoration and other fields.
Patent Information
- Application Number
- CN202510346639.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-24
- Publication Date
- 2025-07-04
AI Technical Summary
The existing honeycomb substrates have environmental problems such as poor biodegradability and high carbon footprint, which cannot meet the growing practical application requirements.
The lignin acetate-plant fiber composite is used to disperse the pulp, soak the lignin acetate solution and heat press to form a high-strength lignin acetate-plant fiber composite material, which is used as a honeycomb substrate for making honeycomb materials.
The prepared lignin acetate-plant fiber composite material has high strength, biodegradability, environmentally friendly and low cost, and is suitable for large-scale industrial production and application, replacing traditional honeycomb substrates.
Smart Images

Figure CN120250397A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and particularly relates to an acetic acid lignin-plant fiber composite material, a preparation method thereof, and an application thereof. Background Art
[0002] Honeycomb materials are a kind of porous composite materials with bionic structural characteristics. Their core structure is a periodically arranged honeycomb-like unit. This special topological structure endows honeycomb materials with excellent mechanical properties and environmental adaptability, making them show important application values in the fields of aerospace, transportation, building decoration, etc. The core advantages of honeycomb materials are reflected in their unique structure-property relationship. The regular arrangement of hexagonal or rectangular honeycomb units enables them to form a high-strength load-bearing structure in the in-plane direction, while maintaining low-density characteristics in the out-of-plane direction. Honeycomb materials not only have a specific strength that can reach 3 to 5 times that of traditional metal materials, but also the energy absorption efficiency can be increased by more than 40% compared with foam materials. In addition, the porous characteristics brought by the honeycomb structure also endow honeycomb materials with excellent sound insulation, heat insulation, and electromagnetic shielding properties, making them irreplaceable in the fields of new energy vehicle battery pack protection, building energy-saving walls, etc.
[0003] At present, the honeycomb base materials applied industrially mainly include the following three categories: 1) Metal base materials (such as: aluminum alloy, titanium alloy): Honeycomb materials based on aluminum alloy occupy more than 80% of the market share in the aviation field due to their high temperature resistance (working temperature can reach 300°C) and high specific stiffness characteristics; 2) Polymer base materials (such as: aramid paper): Honeycomb materials based on aramid paper have excellent flame retardant properties (LOI>28) and corrosion resistance, and are widely used in the field of rail transit; 3) Thermoplastic composite materials (such as: polypropylene composite materials, polycarbonate composite materials): Honeycomb materials based on polypropylene composite materials have a rapid increase in market share to 35% in the field of automotive interior parts due to their thermoformable characteristics (forming temperature is 160°C - 180°C) and low-cost advantages. However, the above honeycomb base materials generally have environmental problems such as poor biodegradability and high carbon footprint, and cannot meet the increasing actual application requirements.
[0004] Therefore, it is of great significance to develop a honeycomb base material with high strength, biodegradability, safety, environmental protection, and low production cost. Summary of the Invention
[0005] The purpose of the present invention is to provide an acetic acid lignin-plant fiber composite material, a preparation method thereof, and an application thereof.
[0006] The technical solution adopted by the present invention is:
[0007] A preparation method of an acetic acid lignin-plant fiber composite material comprises the following steps:
[0008] 1) Add pulp to water for defibration and dispersion, then conduct wet papermaking and drying to obtain paper;
[0009] 2) Dissolve acetic acid lignin in acetic acid solution to prepare an acetic acid lignin solution, then immerse the paper in the acetic acid lignin solution for soaking to obtain wet paper absorbed with acetic acid lignin;
[0010] 3) Dry the wet paper absorbed with acetic acid lignin, and then conduct hot pressing to obtain the acetic acid lignin-plant fiber composite material.
[0011] Preferably, the pulp in step 1) is at least one of waste pulp, unbleached virgin pulp, and bleached virgin pulp.
[0012] Preferably, the concentration of the pulp after defibration and dispersion in step 1) is 0.01 wt% to 3 wt%.
[0013] Preferably, the concentration of the acetic acid solution in step 2) is 0.01 wt% to 3 wt%.
[0014] Preferably, the concentration of the acetic acid lignin solution in step 2) is 0.01 wt% to 5 wt%.
[0015] Preferably, the soaking time in step 2) is 0.1 h to 24 h.
[0016] Preferably, the drying in step 3) is carried out under the condition that the temperature is 50 °C to 100 °C, and the drying time is 1 min to 30 min.
[0017] Preferably, the hot pressing in step 3) is carried out under the conditions that the temperature is 50 °C to 200 °C and the pressure is 0.1 MPa to 50 MPa, and the hot pressing time is 5 min to 60 min.
[0018] An acetic acid lignin-plant fiber composite material is made by the above preparation method.
[0019] A honeycomb material contains the above acetic acid lignin-plant fiber composite material.
[0020] The beneficial effects of the present invention are as follows: The acetic acid lignin-plant fiber composite material of the present invention has the advantages of renewable raw materials, environmental friendliness, high strength, biodegradability, and low production cost. It is suitable as a honeycomb base material for manufacturing honeycomb materials, and its preparation method is simple and easy to control, suitable for large-scale industrial production and application.
[0021] Specifically:
[0022] 1) The present invention uses plant fiber (pulp) as the matrix and acetic acid lignin as the binder. Through a hot pressing process, acetic acid lignin uniformly penetrates into the network of plant fibers and cross-links, thereby obtaining an acetic acid lignin-plant fiber composite material with high tensile strength and stiffness. This acetic acid lignin-plant fiber composite material can be molded as a honeycomb substrate to make a high-strength honeycomb material, which can replace metal / petrochemical-based honeycomb substrates and has broad application prospects;
[0023] 2) The present invention prepares an acetic acid lignin-plant fiber composite material using low-cost acetic acid lignin and plant fiber (pulp) as raw materials. It not only has a low production cost, but also the raw materials are all derived from plants, with the advantages of being renewable and environmentally friendly. The obtained acetic acid lignin-plant fiber composite material is biodegradable and green;
[0024] 3) The preparation method of the acetic acid lignin-plant fiber composite material of the present invention is simple and easy to control, which is conducive to large-scale industrial production and application. Description of the Drawings
[0025] Figure 1 It is a graph showing the ring crush strength test results of the acetic acid lignin-plant fiber composite materials in Examples 1 to 3, the plant fiber materials in Comparative Examples 1 to 3, and the aramid paper in Comparative Example 4.
[0026] Figure 2 It is a tensile stress-tensile strain relationship curve of the acetic acid lignin-plant fiber composite materials in Examples 1 to 3 and the plant fiber materials in Comparative Examples 1 to 3.
[0027] Figure 3 It is a physical picture of the honeycomb material made of the acetic acid lignin-plant fiber composite material in Example 1.
[0028] Figure 4 It is a compressive stress-compressive strain relationship curve of the honeycomb materials made of the acetic acid lignin-plant fiber composite materials in Examples 1 to 3, the plant fiber materials in Comparative Examples 1 to 3, and the aramid paper in Comparative Example 4.
[0029] Figure 5 It is a physical picture of the honeycomb material made of the acetic acid lignin-plant fiber composite material in Example 2.
[0030] Figure 6 It is a physical picture of the honeycomb material made of the acetic acid lignin-plant fiber composite material in Example 3. Detailed Embodiments
[0031] The present invention will be further explained and described below in conjunction with specific embodiments.
[0032] Example 1:
[0033] An acetic acid lignin - plant fiber composite material, and its preparation method is as follows:
[0034] 1) Add waste paper pulp into water, disperse it until the pulp concentration is 0.2 wt%, then carry out wet papermaking to make wet paper, and then dry the wet paper at a temperature of 80 °C for 20 min to obtain paper;
[0035] 2) Dissolve 20 g of acetic acid lignin in acetic acid solution with a concentration of 0.2 wt% to make an acetic acid lignin solution with a concentration of 2 wt%, then immerse the paper into the acetic acid lignin solution, soak for 6 h and then take it out to obtain wet paper absorbed with acetic acid lignin;
[0036] 3) Dry the wet paper absorbed with acetic acid lignin at a temperature of 80 °C for 20 min, and then hot - press it at a temperature of 100 °C and a pressure of 1 MPa for 60 min to obtain the acetic acid lignin - plant fiber composite material (with a thickness of 197 μm and a density of 180 g / m 3 ).
[0037] Performance test:
[0038] 1) Refer to "ISO 12192:2002 Paper and board - Compressive strength - Test method for compressive resistance of paper" to test the ring crush strength of the acetic acid lignin - plant fiber composite material in this example, and the test results are as Figure 1 shown.
[0039] It can be seen from Figure 1 that the ring crush index of the acetic acid lignin - plant fiber composite material is 10.47 Nm / g, indicating its high compressive strength.
[0040] 2) Refer to "ASTM D638 - 2014 Standard test method for tensile properties of plastics" to test the tensile properties of the acetic acid lignin - plant fiber composite material in this example, and the tensile stress - tensile strain relationship curve obtained is as Figure 2 shown.
[0041] It can be seen from Figure 2 that the tensile stress of the acetic acid lignin - plant fiber composite material is 11.90 MPa, indicating its high tensile strength.
[0042] 3) Make the acetic acid lignin - plant fiber composite material in this example into a honeycomb material (the physical diagram is as Figure 3As shown; the honeycomb material is made of multiple acetic acid lignin - plant fiber composites with a length of 152 mm and a width of 12.7 mm. The honeycomb unit is a regular hexagon with a side length of 8 mm. Then, referring to the "ASTM D695 Standard Test Method for Compressive Properties of Rigid Plastics", the compressive properties of the honeycomb material are tested, and the obtained compressive stress - compressive strain relationship curve is as Figure 4 shown.
[0043] It can be seen from Figure 4 that the compressive stress of the honeycomb material is 0.27 MPa, indicating its high compressive strength.
[0044] Example 2:
[0045] An acetic acid lignin - plant fiber composite, and its preparation method is as follows:
[0046] 1) Add softwood pulp to water and disperse it by beating until the softwood pulp concentration is 0.2 wt%, then perform wet forming to make wet paper, and then dry the wet paper at a temperature of 80 °C for 20 min to obtain paper;
[0047] 2) Dissolve 20 g of acetic acid lignin in acetic acid solution with a concentration of 0.2 wt% to make an acetic acid lignin solution with a concentration of 2 wt%. Then immerse the paper in the acetic acid lignin solution and soak it for 36 h, and then take it out to obtain wet paper absorbed with acetic acid lignin;
[0048] 3) Dry the wet paper absorbed with acetic acid lignin at a temperature of 80 °C for 20 min, and then hot - press it at a temperature of 100 °C and a pressure of 1 MPa for 60 min to obtain the acetic acid lignin - plant fiber composite (with a thickness of 227 μm and a density of 188 g / m 3 ).
[0049] Performance test (the test method is the same as that in Example 1):
[0050] 1) The test results of the ring crush strength of the acetic acid lignin - plant fiber composite in this example are as Figure 1 shown, and the tensile stress - tensile strain relationship curve is as Figure 2 shown.
[0051] It can be seen from Figure 1 that the ring crush index of the acetic acid lignin - plant fiber composite is 9.60 Nm / g, indicating its high compressive strength.
[0052] It can be seen from Figure 2 that the tensile stress of the acetic acid lignin - plant fiber composite is 14.10 MPa, indicating its high tensile strength.
[0053] 2) The honeycomb material made of the acetic acid lignin-plant fiber composite material in this embodiment (the physical diagram is as shown in Figure 5 ; the same specifications as in Example 1) The compression stress-compression strain relationship curve is as shown in Figure 4 .
[0054] It can be seen from Figure 4 that the compression stress of the honeycomb material is 0.40 MPa, indicating its high compression strength.
[0055] Example 3:
[0056] An acetic acid lignin-plant fiber composite material, and its preparation method is as follows:
[0057] 1) Add hardwood pulp to water and disperse it until the hardwood pulp concentration is 0.2 wt%, then perform wet papermaking to make wet paper, and then dry the wet paper at a temperature of 80 °C for 20 min to obtain paper;
[0058] 2) Dissolve 20 g of acetic acid lignin in an acetic acid solution with a concentration of 0.2 wt% to make an acetic acid lignin solution with a concentration of 2 wt%, then immerse the paper in the acetic acid lignin solution and soak it for 36 h and then take it out to obtain wet paper absorbed with acetic acid lignin;
[0059] 3) Place the wet paper absorbed with acetic acid lignin at a temperature of 80 °C and dry it for 20 min, and then place it under the conditions of a temperature of 100 °C and a pressure of 1 MPa and hot press it for 60 min to obtain the acetic acid lignin-plant fiber composite material (the thickness is 210 μm, and the density is 164 g / m 3 ).
[0060] Performance test (the test method is the same as in Example 1):
[0061] 1) The test results of the ring crush strength of the acetic acid lignin-plant fiber composite material in this embodiment are as shown in Figure 1 , and the tensile stress-tensile strain relationship curve is as shown in Figure 2 .
[0062] It can be seen from Figure 1 that the ring crush index of the acetic acid lignin-plant fiber composite material is 10.37 Nm / g, indicating its high compressive strength.
[0063] It can be seen from Figure 2 that the tensile stress of the acetic acid lignin-plant fiber composite material is 15.35 MPa, indicating its high tensile strength.
[0064] 2) The honeycomb material made of the acetic acid lignin-plant fiber composite material in this embodiment (the physical diagram is as shown in Figure 6 ; the same specifications as in Example 1) The compression stress-compression strain relationship curve is as shown inFigure 4 as shown
[0065] From Figure 4 it can be seen that the compressive stress of the honeycomb material is 0.39 MPa, indicating its high compressive strength.
[0066] Comparative Example 1
[0067] A plant fiber material, and its preparation method is as follows:
[0068] 1) Add waste paper pulp to water, disperse it by beating until the pulp concentration is 0.4 wt%, then carry out wet papermaking to make wet paper, and then dry the wet paper at a temperature of 90 °C for 15 min to obtain paper;
[0069] 2) Place the paper under the conditions of a temperature of 100 °C and a pressure of 20 MPa for hot pressing for 60 min to obtain the plant fiber material (thickness is 151 μm, density is 100 g / m 3 ).
[0070] Performance test (the test method is the same as that in Example 1):
[0071] 1) The test results of the ring crush strength of the plant fiber material in this comparative example are as Figure 1 shown, and the tensile stress - tensile strain relationship curve is as Figure 2 shown.
[0072] From Figure 1 it can be seen that the ring crush index of the plant fiber material is 4.70 Nm / g, and its compressive strength is much lower than that of the acetic acid lignin - plant fiber composite material in Example 1.
[0073] From Figure 2 it can be seen that the tensile stress of the plant fiber material is 6.30 MPa, and its tensile strength is much lower than that of the acetic acid lignin - plant fiber composite material in Example 1.
[0074] 2) The compressive stress - compressive strain relationship curve of the honeycomb material (with the same specifications as in Example 1) made of the plant fiber material in this comparative example is as Figure 4 shown.
[0075] From Figure 4 it can be seen that the compressive stress of the honeycomb material is 0.18 MPa, and its compressive strength is much lower than that of the honeycomb material made of the acetic acid lignin - plant fiber composite material in Example 1.
[0076] Comparative Example 2
[0077] A plant fiber material, and its preparation method is as follows:
[0078] 1) Dissolve softwood pulp in water and disperse it until the softwood pulp concentration is 0.4 wt%, then perform wet papermaking to make wet paper, and then dry the wet paper at 90 °C for 15 min to obtain paper;
[0079] 2) Place the paper under the conditions of a temperature of 100 °C and a pressure of 20 MPa and hot press for 60 min to obtain the plant fiber material (with a thickness of 166 μm and a density of 100 g / m 3 ).
[0080] Performance test (the test method is the same as that in Example 1):
[0081] 1) The test results of the ring crush strength of the plant fiber material in this comparative example are as Figure 1 shown, and the tensile stress - tensile strain relationship curve is as Figure 2 shown.
[0082] It can be seen from Figure 1 that: the ring crush index of the plant fiber material is 4.28 Nm / g, and its compressive strength is much lower than that of the acetic acid lignin - plant fiber composite material in Example 2.
[0083] It can be seen from Figure 2 that: the tensile stress of the plant fiber material is 9.20 MPa, and its tensile strength is much lower than that of the acetic acid lignin - plant fiber composite material in Example 2.
[0084] 2) The compressive stress - compressive strain relationship curve of the honeycomb material (with the same specifications as in Example 1) made of the plant fiber material in this comparative example is as Figure 4 shown.
[0085] It can be seen from Figure 4 that: the compressive stress of the honeycomb material is 0.15 MPa, and its compressive strength is much lower than that of the honeycomb material made of the acetic acid lignin - plant fiber composite material in Example 2.
[0086] Comparative Example 3:
[0087] A plant fiber material, and its preparation method is as follows:
[0088] 1) Dissolve hardwood pulp in water and disperse it until the hardwood pulp concentration is 0.4 wt%, then perform wet papermaking to make wet paper, and then dry the wet paper at 90 °C for 15 min to obtain paper;
[0089] 2) Place the paper under the conditions of a temperature of 100 °C and a pressure of 20 MPa and hot press for 60 min to obtain the plant fiber material (with a thickness of 154 μm and a density of 100 g / m 3 ).
[0090] Performance test (the test method is the same as that in Example 1):
[0091] 1) The test results of the ring crush strength of the plant fiber material in this comparative example are as Figure 1 shown, and the tensile stress - tensile strain relationship curve is as Figure 2 shown.
[0092] It can be seen from Figure 1 that: the ring crush index of the plant fiber material is 4.13 Nm / g, and its compressive strength is much lower than that of the acetic acid lignin - plant fiber composite material in Example 3.
[0093] It can be seen from Figure 2 that: the tensile stress of the plant fiber material is 9.60 MPa, and its tensile strength is much lower than that of the acetic acid lignin - plant fiber composite material in Example 3.
[0094] 2) The compressive stress - compressive strain relationship curve of the honeycomb material (with the same specifications as in Example 1) made of the plant fiber material in this comparative example is as Figure 4 shown.
[0095] It can be seen from Figure 4 that: the compressive stress of the honeycomb material is 0.16 MPa, and its compressive strength is much lower than that of the honeycomb material made of the acetic acid lignin - plant fiber composite material in Example 3.
[0096] Comparative Example 4:
[0097] Aramid paper (with a thickness of 200 μm and a density of 100 g / m 3 ).
[0098] Performance test (the test method is the same as in Example 1):
[0099] 1) The test results of the ring crush strength of the aramid paper in this comparative example are as Figure 1 shown.
[0100] It can be seen from Figure 1 that: the ring crush index of the aramid paper is 8.52 Nm / g, and its compressive strength is much lower than that of the acetic acid lignin - plant fiber composite materials in Examples 1 - 3.
[0101] 2) The compressive stress - compressive strain relationship curve of the honeycomb material (with the same specifications as in Example 1) made of the aramid paper in this comparative example is as Figure 4 shown.
[0102] It can be seen from Figure 4 that: the compressive stress of the honeycomb material is 0.23 MPa, and its compressive strength is much lower than that of the honeycomb materials made of the acetic acid lignin - plant fiber composite materials in Examples 1 - 3.
[0103] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement methods and are all included in the protection scope of the present invention.
Claims
1. A preparation method of acetic acid lignin-plant fiber composite material, characterized in that, It includes the following steps: 1) Add pulp into water for beating and dispersion, then carry out wet papermaking and drying to obtain paper; 2) Dissolve acetic acid lignin in acetic acid solution to make acetic acid lignin solution, then immerse the paper into the acetic acid lignin solution for soaking to obtain wet paper absorbed with acetic acid lignin; 3) Dry the wet paper absorbed with acetic acid lignin, and then carry out hot pressing to obtain acetic acid lignin-plant fiber composite material.
2. The preparation method according to claim 1, characterized in that: The pulp in step 1) is at least one of waste pulp, unbleached virgin pulp, and bleached virgin pulp.
3. The preparation method according to claim 1 or 2, characterized in that: The concentration of the pulp after beating and dispersion in step 1) is 0.01wt% - 3wt%.
4. The preparation method according to claim 1, characterized in that: The concentration of the acetic acid solution in step 2) is 0.01wt% - 3wt%.
5. The preparation method according to claim 1 or 4, characterized in that: The concentration of the acetic acid lignin solution in step 2) is 0.01wt% - 5wt%.
6. The preparation method according to claim 1 or 4, characterized in that: The soaking time in step 2) is 0.1h - 24h.
7. The preparation method according to claim 1, characterized in that: The drying in step 3) is carried out under the condition of a temperature of 50°C - 100°C, and the drying time is 1min - 30min.
8. The preparation method according to claim 1 or 7, characterized in that: The hot pressing in step 3) is carried out under the conditions of a temperature of 50°C - 200°C and a pressure of 0.1MPa - 50MPa, and the hot pressing time is 5min - 60min.
9. An acetic acid lignin-plant fiber composite material, characterized in that, Made by the preparation method according to any one of claims 1 - 8.
10. A honeycomb material, characterized in that, Comprising the acetic acid lignin-plant fiber composite material according to claim 9.
Citation Information
Patent Citations
Preparation method and application of biodegradable cellulose paper taking lignin as adhesive
CN114016323A
Preparation method and application of lignin / bacterial cellulose hard high-strength nano composite membrane
CN118496547A